Canada's Defence and Security in the Maritime Arctic - Cunje, Ashton B. (Université d'Ottawa | University of Ottawa, 2014)
The purpose of this paper is to examine maritime Arctic states’ defence and security challenges in the maritime Arctic, and more specifically Canada’s defence and security challenges, due to climate change. The three major sections of the paper will consist of: providing the background information and context of challenges that maritime Arctic states will face; situating the maritime Arctic conventional and non-conventional threats to Canada’s context and identifying Canada’s current defence and security capabilities; and presenting recommendations that could improve how Canada operates, from a defence and security perspective, in the maritime Arctic.